Disease prevalence and assosiated pathological changes in small animals presented to post mortem laboratory, Faculty of Veterinary Medicine, UPM from the year 2005 to 2015 - Maniam, Rathiymaler (2016)
Post mortem or necropsy is an autopsy on an animal to find its cause of death whenever it’s possible. The cause of death can be determined using the gross lesions, histopathological changes and laboratory results. Gross changes are the abnormalities observed during post mortem while histopathology involves the abnormal changes in the tissues observed under the microscope. Since keeping pet has become a growing trend among Malaysians, indentifying the common problems leading to death of their furry companion becomes a necessity. This retrospective study was conducted by analyzing data on cases among the small animals which includes cats and dogs presented to Post Mortem Laboratory, Faculty of Veterinary Medicine, UPM to find the most common diseases and to describe the respective lesion associated with the disease. There were a total of 37 diseases diagnosed among dogs. However, the most common diseases among dogs were septicemia (10.2%), mammary gland tumor (8.4%) and Canine Distemper (7.9%) [X2 (34 N=726) = 513.552, p < 0.001)]. In cats, a total of 27 diseases were diagnosed but the most common one were traumatic injuries (19.5%), Feline Infectious Peritonitis (15.1%) and Sporotrichosis (12%) [X2 (26 N=726) = 1568, p < 0.001)]. Each of the diseases has their specific gross pathology and histopathological lesion which are discussed below.